PPO-ZIF MMMs possessing metal-polymer interactions for propane/ propylene separation - Kunjattu, H. Shebeeb; Kharul, Ulhas K. (Journal of Membrane Science, 2023)
An assertive formation of ZIF-based mixed matrix membranes (MMMs) with polyphenylene oxide (PPO), a high permeability polymer as a host, is presented. The interfacial interactions between the filler particles and polymer matrix are established by DSC and XPS analyses. The ZIF loading could be achieved up to 40% without hampering the stability of the resulting MMMs. These membranes were evaluated for pure gas permeability, specifically aiming at C3H6/C3H8 separation, a highly desired application in industry. The ZIF-PPO hybrids display promising pure gas as well as mixed gas permeation performance. The 40% ZIF-8 and ZIF-67 loaded membrane display promising C3H6/C3H8 selectivity of 27.5 and 25, with a permeability of 12 and 13 barrer, respectively. The enhanced selectivity is attributed to the absence of defects eliminated due to metal-polymer interactions. The permeation study of a 30% ZIF-8 loaded membrane while varying transmembrane pressure and long-time exposure (150 h) of propylene at 60 psi indicated the excellent stability of the membrane. The sorption analysis further confirmed the molecular sieving characteristics of the ZIF@PPO MMMs. The mixed gas permeation performance showed promising results of high permeability as well as maintaining selectivity over a wide range of compositions.
Keywords: Interfacial interactions; Mixed matrix membrane; Olefin-paraffin separation; poly(phenyleneoxide); Zeolitic imidazole framework